Progressive cystic lesion in a middle-aged patient with tuberous sclerosis complex: A case report. Issue 15 (April 2018) - Zhang, Le; Jiang, Xin-Yue; Chen, Ni; Hao, Nan-Ya; Zhou, Dong; Li, Jin-Mei
Abstract: Rationale: Tuberous sclerosis complex (TSC) is an uncommon multiple systems disorder. The main characteristics of the disease in the central nervous system include cortical or subcortical tubers, subependymal nodules, and subependymal giant cell astrocytoma. However, progressive cystic lesions in the cerebral hemispheres have rarely been reported in previous studies of TSC. Patient concerns: We present the case of a 35-year-old man with TSC who was admitted to our hospital for a sudden attack of serious headache, vomiting, and left hemiplegia. Brain computerized tomography and magnetic resonance imaging (MRI) revealed multiple subependymal calcific nodes and multiple cystic lesions in the right frontal, temporal, and parietal lobes. The solid nodule in the lesion demonstrated contrast enhancement. Diagnoses: The patient was diagnosed with TSC, but the properties of the cystic lesion in the brain were unclear and a tumor was suspected. Interventions: Emergency operation was performed immediately. Pathological examination of the lesion revealed a vascular malformation, but no tumor cells. Outcomes: In the fourth year after the surgery, brain MRI revealed a relapse of the cystic mass and surgery was suggested again. However, the patient refused to undergo surgery again. Lessons: This case describes an atypical MRI presentation of TSC occurring in middle-age. This condition can cause a life-threatening condition and may recur after surgery. Our finding emphasizes the importance of neuroimaging surveillance in patients older than 25 years old and after lesion resection.